Representation of Dayak culture in Sarawak’s modern paintings / Natasha Rusdy Wong - Natasha , Rusdy Wong (2018)
This dissertation explores the representation of Dayak culture in modern paintings painted by seven selected artists. The selected artists consist of four Dayak, and three non-Dayak artists who are all currently residing in Sarawak, East Malaysia. The main objective is to determine the approaches to representation of Dayak culture that the selected artists may have applied in creating their paintings. Stuart Hall’s theory of three different approaches to representation serves as the theoretical framework within this study, which are: (1) reflective approach, (2) intentional approach, and (3) constructive approach. This research includes the selected artists’ artworks and sessions of semi-structured interviews with the artists themselves. Visual analysis of the selected artworks reveal the difference in the formalistic approaches to representation presented by the seven selected artists, and the narratives gained from the semi-structured interviews with them gave further insights on why the Dayak culture serve as such significant inspirations and influences for the selected artists. Through this research, it is determined that there is an apparent difference in the approaches to representation that each selected artist employs into the creation of their representation of the Dayak culture. The formalistic analysis of the selected paintings revealed that there is a significant difference in how the four selected Dayak artists and three selected non-Dayak artists represent Dayak culture. The selected Dayak artists are inspired by the local flora, fauna and landscape around them, and thus, are more inclined towards abstraction in their representation of Dayak culture. On the other hand, the selected non-Dayak artists are inspired by their observations and research of the Dayak culture, and thus, tend to focus on figurative representation of the Dayak culture such as depicting the Dayak native lifestyles and depicting the elements that are related to Dayak culture, such as the Dayak’s traditional headgear and beads. A further theoretical analysis demonstrates that the approaches to representation employed by each of the selected artists are determined by their perceptions of the Dayak culture, which subsequently affects the formalistic approaches and selection of subject matter.